A Biodegradable Iridium(III) Coordination Polymer for Enhanced Two‐Photon Photodynamic Therapy Using an Apoptosis–Ferroptosis Hybrid Pathway. (24th May 2022) - Ke, Libing; Wei, Fangmian; Xie, Lina; Karges, Johannes; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract: The clinical application of photodynamic therapy is hindered by the high glutathione concentration, poor cancer‐targeting properties, poor drug loading into delivery systems, and an inefficient activation of the cell death machinery in cancer cells. To overcome these limitations, herein, the formulation of a promising Ir III complex into a biodegradable coordination polymer (IrS NPs ) is presented. The nanoparticles were found to remain stable under physiological conditions but deplete glutathione and disintegrate into the monomeric metal complexes in the tumor microenvironment, causing an enhanced therapeutic effect. The nanoparticles were found to selectively accumulate in the mitochondria where these trigger cell death by hybrid apoptosis and ferroptosis pathways through the photoinduced production of singlet oxygen and superoxide anion radicals. This study presents the first example of a coordination polymer that can efficiently cause cancer cell death by apoptosis and ferroptosis upon irradiation, providing an innovative approach for cancer therapy. Abstract : A biodegradable iridium(III) coordination polymer IrS NPs was developed to trigger an apoptosis and ferroptosis hybrid cell death pathway and achieve tumor suppression in two‐photon photodynamic therapy. Additionally, the changes in luminescence lifetime between monomer and polymer allow phosphorescence lifetime imaging microscopy (PLIM) imaging for targeted photodynamic therapy (PDT). These properties combine to make IrS NPs highly effective anticancer PDT agents.